Komunikasi Multiaktor Untuk SDGS 12 : Komunikasi Pemerintah, Komunitas dan Masyarakat Dalam Program Bank Sampah Sukamaju Sejahtera - Nasywa Izra; Alsha Nuraini; Adam Aulia Manzal Khan (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2025)
Waste is a serious problem faced by many countries around the world, especially Indonesia. However, the presence of the Sukamaju Sejahtera Waste Bank program from West Bandung Regency has attracted significant attention because it has the potential to be an innovation that can reduce the problem of plastic waste. This paper will examine the importance of the involvement of various actors, including the government, communities, and the public, in empowering the Sukamaju Sejahtera Waste Bank as a solution to address the plastic waste problem in Indonesia. This research will use a literature review method to deeply examine the relationship between the importance of communication with these various actors. The findings of this study demonstrate that multi-actor communication plays a crucial role that must be maintained in developing the existence of the Sukamaju Sejahtera Waste Bank. However, this communication must also be accompanied by tangible forms of assistance so that the waste bank does not lose its ability to continue processing plastic waste in Indonesia.